Strength analysis for designing a bicycle transmission system without chain. Issue 1 (December 2020) - Billianto, Kevin; Purna Irawan, Agustinus; Halim, Agus; Abdullah, M. Z.; Chin Lin, Linda Lin; Baskara, Gregorius Dimas
Abstract: Bicycles have several advantages over other transportation, one of which is its environmentally-friendly characteristic. The strength analysis consists of a series of strength calculations and simulations to save time and cost in the component design of a bicycle transmission system without chains. The design of a bicycle transmission system without a chain uses the French method, which begins by analyzing the needs based on a transmission system that already exists in the field and ends with a working picture of the strength analysis of a modified bicycle that has a chainless transmission system. The design of a bicycle transmission system without a chain is divided into two types of designs using the principle of the four connecting rod mechanism. Analysis of the power design shows that the two types of design of a bicycle transmission system without a chain work well as a bicycle transmission system.